PENGARUH KUALITAS PRODUK & HARGA TERHADAP KEPUTUSAN MEMBELI (STUDI PADA KONSUMEN DODOL SALAK PRODUKSI DESA PANGU) - Kapahang, Nela Favianury; Tampi, Johny. R.E.; Rogahang, Joula. J. (Sam Ratulangi University, 2016)
Abstract :This study is based on that first (horticultural) product such as fruits can be processed into products dodol salak. Quality Product and price influnce on purchasing decision. As for the formulation of the problem in this study is whether there is influence in quality product price and purchasing decisions. The Purpose of this study was to analyze the effect of induced quality product and purchasing decisions This Study use descriptive Quantitative approach Correlation and Regression Analysis. These samples included 50 respondens from the consumer population dodol salak In Pangu Village. Results of the study found that the regression equation is formed Y= 8,875 + 0,115 X1 + 0,651 X2. The Results showed that the quality of products has a great influnce on purchasing sdecisions The Results of research and discussion of the variabel quality product and price has significcan simultaneous influence on purchasing decision dodol salak Keywords: Quality Product, Price, & Purchasing Decisions